Changes in the provision of institutionalized mental health care in post-communist countries. - Adrian P Mundt (Public Library of Science (PLoS), 2012)
Background General psychiatric and forensic psychiatric beds, supported housing and the prison population have been suggested as indicators of institutionalized mental health care. According to the Penrose hypothesis, decreasing psychiatric bed numbers may lead to increasing prison populations. The study aimed to assess indicators of institutionalized mental health care in post-communist countries during the two decades following the political change, and to explore whether the data are consistent with the Penrose hypothesis in that historical context. Methodology/principal findings General psychiatric and forensic psychiatric bed numbers, supported housing capacities and the prison population rates were collected in Azerbaijan, Belarus, Croatia, Czech Republic, East Germany, Hungary, Kazakhstan, Latvia, Poland, Romania, Russia and Slovenia. Percentage change of indicators over the decades 1989-1999, 1999-2009 and the whole period of 1989-2009 and correlations between changes of different indicators were calculated. Between 1989 and 2009, the number of general psychiatric beds was reduced in all countries. The decrease ranged from -11% in Croatia to -51% in East Germany. In 2009, the bed numbers per 100,000 population ranged from 44.7 in Azerbaijan to 134.4 in Latvia. Forensic psychiatric bed numbers and supported housing capacities increased in most countries. From 1989-2009, trends in the prison population ranged from a decrease of -58% in East Germany to an increase of 43% in Belarus and Poland. Trends in different indicators of institutionalised care did not show statistically significant associations. Conclusions/significance After the political changes in 1989, post-communist countries experienced a substantial reduction in general psychiatric hospital beds, which in some countries may have partly been compensated by an increase in supported housing capacities and more forensic psychiatric beds. Changes in the prison population are inconsistent. The findings do not support the Penrose hypothesis in that historical context as a general rule for most of the countries.